Children Exhibit a More Comparable Neuromuscular Fatigue Profile to Endurance Athletes Than Untrained Adults - Bontemps, Bastien; Piponnier, Enzo; Chalchat, Emeric; Blazevich, Anthony J.; Julian, Valérie; Bocock, Olivia; Duclos, Martine; Martin, Vincent; Ratel, Sébastien (Frontiers in Physiology, 2019)
The present study compared neuromuscular fatigue profiles between children, untrained adults and adult endurance athletes during repeated maximal muscle contractions. Eighteen prepubertal boys, 19 untrained men and 13 endurance male athletes performed 5-s maximal voluntary isometric knee extensor contractions (MVICs) interspersed with 5-s recovery until MVIC reached 60% of its initial value. Single and doublet magnetic stimulations were delivered to the femoral nerve to quantify the time course of potentiated twitch amplitude (Ttw,pot), high-frequency torque (T100Hz) and the low-to-high frequency torque ratio (T10Hz/T100Hz), i.e., indicators of peripheral fatigue. M-wave-normalized EMG amplitudes (EMG/M) and the maximal voluntary activation level (VA) were calculated to quantify central fatigue. Adults (15.9 ± 3.9 repetitions) performed fewer MVICs than children (40.4 ± 19.7) and endurance athletes (51.7 ± 19.6), however, no difference was observed between children and athletes (P = 0.13). Ttw,pot (∼52%, P < 0.001), T100Hz (∼39%, P < 0.001) and T10Hz/T100Hz (∼23%, P < 0.001) decreased only in adults. Similar decrements in vastus medialis and vastus lateralis EMG/M were observed in children and endurance athletes (range: 40–50%), and these were greater than in adults (∼15%). Whilst VA decreased more in children (-38.4 ± 22.5%, P < 0.001) than endurance athletes (-20.3 ± 10.1%, P < 0.001), it did not change in adults. Thus, children fatigued more slowly than adults and as much as endurance athletes. They developed less peripheral and more central fatigue than adults and, although central fatigue appeared somewhat higher in children than endurance athletes, both children and endurance athletes experienced greater decrements than adults. Therefore, children exhibit a more comparable neuromuscular fatigue profile to endurance athletes than adults.